2020
DOI: 10.17159/2310-3833/2020/vol50n1a6
|View full text |Cite
|
Sign up to set email alerts
|

Being a mother of a child with HIV-related Neurodevelopmental Disorders in the Zimbabwean Context

Abstract: BACKGROUND: There is a growing population of mothers caring for their biological children who are infected with Human Immunodeficiency Virus (HIV), in Zimbabwe. Many of these children present with HIV-related Neuro Developmental Delays (NDDs). The occupation of being a mother is a complex and multifaceted role geared towards caring for and nurturing children. The different ways in which mothers negotiate the unique circumstances linked to the occupation of being a mother to a child with diagnosis of HIV-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Similar findings were echoed from caregivers of children with congenital heart diseases who reported that they spent more time with their children (Sabzevari & Nematollahi, 2016) because more is required in the care of their children. Another study pointed out that caregivers wanted to be with their children most of the time, as a way of protecting them from stigma that is commonly associated with being diagnosed with HIV/Aids (Munambah et al., 2020). Caregiver involvement in the play of their children has potential to hamper or promote play.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were echoed from caregivers of children with congenital heart diseases who reported that they spent more time with their children (Sabzevari & Nematollahi, 2016) because more is required in the care of their children. Another study pointed out that caregivers wanted to be with their children most of the time, as a way of protecting them from stigma that is commonly associated with being diagnosed with HIV/Aids (Munambah et al., 2020). Caregiver involvement in the play of their children has potential to hamper or promote play.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly, there is a paucity of literature on children's play in this context. One of the few studies on the caring occupation for children with HIV/AIDS in Zimbabwe reported that due to fear of stigma, guiltiness and self‐blame, caregivers were not willing to share their caregiving role with anyone instead their everyday doings were centred on care and protecting the children from stigma and possibilities of further harm (Munambah et al., 2020). Developing a better understanding of the play profile would improve the use of play as both an intervention outcome, as well as a medium for delivering intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In the model of children's play by Cooper (2000), the context is referred to as both the child's immediate environment (physical setting, available play materials, and social elements) and the surrounding cultural values and beliefs. A study conducted in Zimbabwe with caregivers caring for a child with HIV-related neurodevelopmental delays revealed that cultural and spiritual beliefs, as well as fear of stigma, impacts on how caregivers support and influence the play of their children with HIV/Aids (Munambah, Gretschell, & Sonday, 2020). Stigma, coupled with poverty, further adds to the burden of caring for a child with HIV/Aids in low-resourced settings (Steinert et al, 2017).…”
Section: Conceptual Framework: Model Of Children's Playmentioning
confidence: 99%
“…10,11 Evidence suggests HIV-associated neuro-developmental delays among CLWHA. 12 Earlier studies have shown that caregivers experience severe burdens in Nigeria, 13 rural Malawi, 14 and Southern India. 15 Even in areas where there are reported mild/moderate burdens such as in Calabar Nigeria 16 and Malaysia, 17 caregivers express concerns of caring having a toll on their finances and psychological and physical health.…”
Section: Introductionmentioning
confidence: 99%
“…For children living with HIV/AIDS (CLWHA), the role of the caregivers becomes painstaking due to the likelihood of dependency of the children on activities daily 10,11 . Evidence suggests HIV‐associated neuro‐developmental delays among CLWHA 12 . Earlier studies have shown that caregivers experience severe burdens in Nigeria, 13 rural Malawi, 14 and Southern India 15 .…”
Section: Introductionmentioning
confidence: 99%